Auer rod-positive acute leukemia with predominantly lymphoid immunophenotype: Report on 11 cases and review of literature - Hrusak, Ondrej; Stancikova, Jitka; Vodickova, Elena; Podolska, Tereza; Möricke, Anja; Attarbaschi, Andishe; Dworzak, Michael; Sestakova, Zuzana; Svec, Peter; Zaliova, Marketa Kubricanova; Janotova, Iveta; Zapletal, Ondrej; et al. (Pediatric blood & cancer, 2025)
BACKGROUND: Auer rods (AuRs) are prominent intracellular structures found almost exclusively in myeloid cell malignancies, such as acute myeloid leukemia (AML), chronic and juvenile myelomonocytic leukemia and myelodysplastic syndrome. Extremely rare AuRs have been reported in patients with acute lymphoblastic leukemia (ALL) or among ambiguous lineage leukemia patients with a dominantly lymphoblastic immunophenotype. PROCEDURE: We report diagnostic and follow-up data of an international cohort of 11 children suffering from leukemias with AuRs and with significant presence of T and myeloid markers, majority of whom categorized as early T-cell precursor (ETP, n = 7); or T-ALL (ETP status unknown, n = 2), ALAL (acute leukemia of ambiguous lineage, n = 1), and AML reclassified from ALAL (n = 1). We described other diagnostic details and treatment types and responses. Moreover, we summarize previously published data. RESULTS: Among the four patients who started and remained on ALL-type therapy, all were in the first complete remission, whereas both patients who started and remained on AML-type therapy relapsed and died. Of the patients who followed either a combined ALL/AML protocol (Interfant 06) or who switched from one of the two types of therapy to the other, one patient died, and the remaining four were in first complete remission at the most recent follow-up. We also searched for similar cases in the literature and found only three additional children with nonmyeloid leukemia and AuRs and 10 adults with this type of leukemia. CONCLUSIONS: Briefly, ALL- or combined ALL/AML-type therapy may be effective for treating AuR-positive leukemia patients with a lymphoid immunophenotype.
Keywords: Leukemia, Myeloid, Acute; Infant; Humans; kojenec; dítě; Child; následné studie; Female; imunofenotypizace; lidé; předškolní dítě; Immunophenotyping; ženské pohlaví; Male; Adolescent; akutní lymfatická leukemie; mužské pohlaví; Child, Preschool; Precursor Cell Lymphoblastic Leukemia-Lymphoma; akutní myeloidní leukemie; Follow-Up Studies; mladiství